2019
DOI: 10.1589/jpts.31.360
|View full text |Cite
|
Sign up to set email alerts
|

Sexual disability in patients with chronic non-specific low back pain—a multicenter retrospective analysis

Abstract: [Purpose] Oswestry Disability Index includes an item (Oswestry Disability Index-8) aiming to assess sexual disability associated to low back pain. The aim of this study is to investigate the percentage of participants who answered the Oswestry Disability Index-8, and the relevance and characteristics of sexual disability due to low back pain in Italian patients. [Participants and Methods] Design: multicenter retrospective analysis. Population: six hundred and ninety-seven outpatients with non-specific low back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
9
0
2
Order By: Relevance
“…We found that this association was identified in a study of chronic nonspecific low back pain. 41 Since the internal iliac artery is shallow and easily anastomosed with the graft vessels and its blood flow vessel meets the needs for blood perfusion flow of the graft kidney, generally speaking, the graft kidney is usually transplanted in the fossa iliac on one side of the patient's lower abdomen, which is adjacent to the sexual organ (ie, vagina and testis). Many patients are found afraid to have sex for fear of colliding or damaging the graft through physicians' interviews with them, 20,42 thereby presenting a low frequency of sexual intercourse after KT.…”
Section: Discussionmentioning
confidence: 99%
“…We found that this association was identified in a study of chronic nonspecific low back pain. 41 Since the internal iliac artery is shallow and easily anastomosed with the graft vessels and its blood flow vessel meets the needs for blood perfusion flow of the graft kidney, generally speaking, the graft kidney is usually transplanted in the fossa iliac on one side of the patient's lower abdomen, which is adjacent to the sexual organ (ie, vagina and testis). Many patients are found afraid to have sex for fear of colliding or damaging the graft through physicians' interviews with them, 20,42 thereby presenting a low frequency of sexual intercourse after KT.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of SD is inversely proportional to the intensity of the accompanying pain. To find out how common and relevant sexual impairment caused by LBP is, Ferrari et al [14] conducted research to find out how many Italian patients reported that their sexual life was affected by pain in some way, just as in other countries. When it comes to persistent low back pain and female sexual function, Drummond et al [11] found no connection.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of SPL in terms of disability in activities of daily living (ADLs), including impact on sexual activity, can be assessed using the Oswestry Disability Index [ 35 ], which has demonstrated strong metric properties also in symptomatic lumbar SPL [ 36 ]. Other questionnaires useful for the assessment of cognitive-behavioural obstacles to recovery are: Fear Avoidance Beliefs Questionnaire and the Tampa Scale for fear of movement; the Coping Strategies Questionnaire and the Chronic Pain Coping Index for coping; the Pain Self-Efficacy Questionnaire for self-efficacy, the Pain Catastrophizing Scale, and the revised version of the Coping Strategies Questionnaire for catastrophizing [ 37 ].…”
Section: Assessmentmentioning
confidence: 99%